Dreamer in dialogue - Novák, Caterina (Acta neophilologica, 2013)
The aim of this article is to explore the parallels between two late-nineteenth-century utopias,William Henry Hudsons A Crystal Age (1882) and William Morriss News from Nowhere (1891). Itaims to explore how these two works respond to the transition from a kinetic to a static conception ofutopia that under pressure from evolutionary and feminist discourses took place during the period.Particular focus lies on the way in which this is negotiated through the depiction of evolution, sexuality,and gender roles in the respective novels, and how the depiction of these disruptive elements may workas a means of ensuring the readers active engagement in political, intellectual and emotional terms.
Keywords: angleška književnost; English literature; evolucija; evolution; gender roles; Hudson, William Henry; literarne študjie; literary studies; Morriss, William; spolne vloge; utopian fiction; utopična književnost